Upaya Meningkatkan Hasil Belajar Ekonomi dengan Menggunakan Media Audio Visual Pada Peserta Didik Kelas XI MA Miftahul Jannah Palangka Raya - Trisnawati Trisnawati; Muhammad Andi Setiawan (Bitnet: Jurnal Pendidikan Teknologi Informasi, 2018)
This study aims to determine the Improvement of Learning Outcomes and Learning Activities of Class XI students of Madrasah Aliyah Miftahul Jannah Palangakaraya using audiovisual media. The type of research used in this study is Classroom Action Research (CAR). The instruments of data collection in this study were observation and tests. While the data analysis techniques in this study used the classical and individual completeness percentage formula. The results of the study: (1) Learner Activities Learning Madrasah Aliyah class XI Miftahul Jannah Palangkaraya at the time of economic learning using audiovisual media is more active, (2) There is an increase in learning outcomes of students of class XI Economics Madrasah Aliyah Miftahul Jannah Palangkaraya after using Audio-Visual Media.